PENGELOLAAN KOMPETENSI PROFESIONAL DALAM MENINGKATKAN MUTU PENDIDIKAN SD DI KECAMATAN RANTAU KABUPATEN ACEH TAMIANG - Nurjanah Nurjanah; Siraj Siraj; Munawar Munawar (Hijri, 2025)
This study was motivated by the need for effective management of teachers' professional competence to improve the quality of education at the elementary school level, particularly at SD Negeri 2 Rantau Pauh and SD Negeri Kampung Durian in Rantau Subdistrict, Aceh Tamiang Regency. The management of teachers' professional competence is considered crucial due to the existing variations in teachers' abilities in lesson planning, classroom instruction, and the use of evaluation results as a basis for instructional improvement. Therefore, this study focuses on the planning, implementation, evaluation, and follow-up of professional competence management in improving the quality of education. This research employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation. The research subjects included principals, teachers, and school committee members. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results of the study indicate that: (1) the planning of teachers' professional competence management was based on the results of classroom supervision, student learning outcomes, and the school quality report, although it was implemented gradually due to limited resources; (2) the implementation of professional competence development was carried out adaptively through internal school strengthening strategies, such as direct mentoring, peer learning, reflective discussions, and the utilization of the Teacher Working Group (KKG), even though external training had not been evenly attended by all teachers; (3) the evaluation of teachers' professional competence emphasized reflection on teaching practices and professional responsibility, rather than being solely oriented toward fulfilling instructional administrative requirements; and (4) follow-up actions were implemented through continuous guidance and mentoring using a humanistic coaching approach, although they were not yet fully supported by systematic written follow-up plans. These findings indicate that the contextual, adaptive, and sustainable management of teachers' professional competence can support the improvement of educational quality at the elementary school level.